Chronic rejection of human face allografts. Issue 4 (10th November 2018) - Krezdorn, Nicco; Lian, Christine G.; Wells, Michael; Wo, Luccie; Tasigiorgos, Sotirios; Xu, Shuyun; Borges, Thiago J.; Frierson, Rayven M.; Stanek, Ewelina; Riella, Leonardo V.; Pomahac, Bohdan; Murphy, George F.
Abstract : Face vascularized composite allografts (FVCAs) have helped patients with severe facial disfigurement, with acute rejection now largely controlled through iatrogenic immunosuppression. However, little is known regarding the incidence and mechanism(s) of more long‐term pathologic alterations in FVCAs that may affect function and graft durability. Protocol surveillance biopsy specimens for up to an 8‐year interval in 7 patients who received FVCAs at our institution revealed histopathologic evidence of chronic rejection. Clinical manifestations included features of premature aging, mottled leukoderma accentuating suture lines, telangiectasia, and dryness of nasal mucosa. Pathologic changes consisted of epidermal thinning accompanied by discrete foci of lymphocyte‐mediated cytotoxicity, hyperkeratosis, follicular plugging, vascular ectasia, and sclerosis beneath the epidermal layer associated with collagen type I deposition. Genomic interrogation and immunohistochemistry of sclerotic zones revealed upregulation of the AP‐1 pathway components, JunB and c‐Fos, previously implicated in overproduction of type I dermal collagen in the setting of systemic sclerosis. We conclude that some patients develop chronic rejection in FVCAs with striking similarities to alterations seen in certain autoimmune cutaneous disorders (lupus erythematosus and scleroderma/chronic sclerodermoid graft‐versus‐host disease). Identification of relevant pathways and genes, such as JunB and c‐Fos, may provide new targets for preventative therapies for chronic immune‐mediated changes in vascularized composite allografts. Abstract : Biopsies of face transplant recipients reveal chronic rejection similar to certain autoimmune cutaneous diseases.